Pharmacodynamic Effects of Aripiprazole and Ziprasidone with Respect to P-Glycoprotein Substrate Properties - Holthoewer, D.; Kirschbaum, K. M.; Frisch, J.; Hiemke, C.; Schmitt, U. (Pharmacopsychiatry, 2013)
Aripiprazole, an atypical antipsychotic drug with mixed antagonism and agonism on dopamine D2 and serotonin receptors, is a substrate of the efflux transporter P-glycoprotein (P-gp). Here we tested the pharmacodynamic consequences of these properties in a P-gp deficient mouse model by studying the effects of aripiprazole and of ziprasidone on motor coordination.The motor behaviour of wild-type (WT) and P-gp deficient [abcb1ab(−/−)] mice was investigated on a RotaRod. Mice received acute injections of either aripirazole or ziprasidone. For comparison, the dopamine receptor antagonist haloperidol and serotonin receptor ligands buspirone and ketanserin were also applied.Pharmacokinetic analyses revealed P-gp activity for aripiprazole and ziprasidone. This was indicated by 3.1- and 1.9-fold higher ratios of brain to plasma concentrations of drugs in knock-out to WT animals. Acute doses of ariprazole or ziprasidone impaired motor behaviour on the RotaRod. Effects were similar after injection of haloperidol, whereas the serotonin receptor ligands buspirone and ketanserin enhanced RotaRod performance. Genotype dependent differences of motor performance were found for aripiprazole but not for ziprasidone.Evidence was given that P-gp substrate properties have pharmacodynamic consequences for aripiprazole but not for ziprasidone and thus affect dopamine receptor related motor behaviour.
Keywords: antipsychotics; P-glycoprotein; knock-out; pharmacokinetics; pharmacodynamics